A multilayered microfluidic blood vessel-like structure - Hasan, Anwarul (Biomed Microdevices, 2015)
There is an immense need for tissue engineered blood vessels. However, current tissue engineering approaches still lack the ability to build native blood vessel-like perfusable structures with multi-layered vascular walls. This paper demonstrated a new method to fabricate tri-layer biomimetic blood vessel-like structures on a microfluidic platform using photocrosslinkable gelatin hydrogel. The presented method enables fabrication of physiological blood vessel-like structures with mono-, bi- or tri-layer vascular walls. The diameter of the vessels, the total thickness of the vessel wall and the thickness of each individual layer of the wall were independently controlled. The developed fabrication process is a simple and rapid method, allowing the physical fabrication of the vascular structure in minutes, and the formation of a vascular endothelial cell layer inside the vessels in 3–5 days. The fabricated vascular constructs can potentially be used in numerous applications including drug screening, development of in vitro models for cardiovascular diseases and/or cancer metastasis, and study of vascular biology and mechanobiology.